ANALYZE THE INFLUENCE OF THE TECHNOLOGY ACCEPTANCE MODEL (TAM) ON THE USE OF FINTECH LENDING - Theresia Trisanti (LPPM STIE YKPN Yogyakarta, 2024)
This study endeavors to explore the impact of perceived usefulness and perceived ease of use on the intention to use fintech lending applications in Indonesia. The independent variables under scrutiny are perceived usefulness and perceived ease of use, while the dependent variable is the adoption of fintech lending applications. Employing a quantitative approach, this research employs a descriptive methodology. Primary data collected from 182 respondents serves as the basis for analysis. Sampling in this study is conducted using a non-probability technique, specifically the purposive sampling method. Questionnaires are distributed based on specific criteria, targeting individuals who have utilized fintech lending applications and reside in Indonesia. The findings, derived from multiple regression analysis, reveal a significant positive correlation between perceived usefulness, perceived ease of use, and the adoption of fintech lending applications in Indonesia. The research concludes that users use fintech lending technology when they find it easy to access loan funds quickly and when the application features do not ask for various types of information and documents.